2020
DOI: 10.1002/nop2.477
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the influence of clinic funding on the integration of family practice nurses in Newfoundland and Labrador

Abstract: Aim This study explores the contributions of family practice nurses in primary care across Newfoundland and Labrador funded by fee‐for‐service and alternate payment plans to examine the influence of funding arrangements on nursing roles/activities. Design A qualitative descriptive design was employed. Methods Semi‐structured telephone interviews were conducted between March‐July 2018 with physicians and Registered Nurses working in primary care settings in Newfoundland and Labrador. Interviews were transcribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In our original study ( Mathews et al, 2020 ), eight interviews were conducted (five family practice nurses and three family physicians; six females and two males), ranging from 19–36 minutes in length. Participants worked in a variety of settings, including fee-for-service and globally-funded practices, and in both rural and urban communities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our original study ( Mathews et al, 2020 ), eight interviews were conducted (five family practice nurses and three family physicians; six females and two males), ranging from 19–36 minutes in length. Participants worked in a variety of settings, including fee-for-service and globally-funded practices, and in both rural and urban communities.…”
Section: Resultsmentioning
confidence: 99%
“…We found substantial variation in the expression of professional competencies among the participants in our study. Our original study found that the funding model under which family practice nurses work in NL influences the nature and scope of their role ( Mathews et al, 2020 ). Across Canada, provinces use a variety of funding models to finance family practice nurses, including global funding, capitation, and enhanced fee-for-service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations